2023
DOI: 10.1007/s11882-022-01059-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of SARS-CoV-2 Infection of Nasal Respiratory and Olfactory Epithelia and Its Clinical Impact

Abstract: Purpose of Review While the predominant cause for morbidity and mortality with SARS‐CoV‐2 infection is the lower respiratory tract manifestations of the disease, the effects of SARS-CoV-2 infection on the sinonasal tract have also come to the forefront especially with the increased recognition of olfactory symptom. This review presents a comprehensive summary of the mechanisms of action of the SARS-CoV-2 virus, sinonasal pathophysiology of COVID-19, and the correlation with the clinical and epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 121 publications
(176 reference statements)
0
9
0
Order By: Relevance
“…The post-COVID and the long-term-COVID have both tremendously triggered a lot of complications in different human systems. The loss or reduction of smell, among other complications of the nervous system, is an associated symptom for patients affected by different variants of COVID-19, including the omicron variant [ 102 , 103 , 104 , 105 , 106 ]. Moreover, studies reported that the prevalence of olfactory dysfunction differs greatly between populations and approaches [ 106 , 107 , 108 ].…”
Section: Mechanisms Of Sars-cov-2 Mediating the Loss Of Smellmentioning
confidence: 99%
“…The post-COVID and the long-term-COVID have both tremendously triggered a lot of complications in different human systems. The loss or reduction of smell, among other complications of the nervous system, is an associated symptom for patients affected by different variants of COVID-19, including the omicron variant [ 102 , 103 , 104 , 105 , 106 ]. Moreover, studies reported that the prevalence of olfactory dysfunction differs greatly between populations and approaches [ 106 , 107 , 108 ].…”
Section: Mechanisms Of Sars-cov-2 Mediating the Loss Of Smellmentioning
confidence: 99%
“…The Omicron variant of SARS-CoV-2 was first detected in South Africa in November 2021, and became the main epidemic strain in the world by 15 January 2022 (11,12) . Some studies have found that the Omicron variant causes less smell and taste dysfunction than non-Omicron SARS-CoV-2 (1315) . Further, a meta-analysis found that the prevalence rates of olfactory dysfunction caused by the Omicron variant are 8%–17% and 2%–17% the in UK and USA, respectively (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Omicron variant, which firstly detected in South Africa in November 2021, has become the main epidemic strain in the world by 15 January 2022 (Menni et al 2022;Hu et al 2022). Some studies found that Omicron variant cause less smell and taste dysfunction than Non-omicron (Chee et al 2023;Rodriguez-Sevilla, Güerri-Fernádez, and Bertran Recasens 2022;von Bartheld and Wang 2023). According to a Meta-Analysis, the prevalence of olfactory dysfunction caused by the Omicron variant is 8-17% and 2-17% separately in UK and USA (von Bartheld and Wang 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The number of confirmed COVID-19 cases reported to the World Health Organization (WHO) by November 30, 2022 was 639 million (WHO Coronavirus (COVID-19) Dashboard, https://covid19.who.int/), but the true number of cases is believed to be much higher, at about 3.4 billion in October 2021 [5]. A total of 6 billion cases – after the global spread of the more infectious omicron variant – has been estimated in October 2022 [6], Since the prevalence of olfactory dysfunction differs between virus variants [1-4,7,8], it is important for estimates of the current global and regional prevalence of olfactory dysfunction to take properties of different virus variants into account. It has been argued that, even though omicron may cause a lower prevalence of olfactory dysfunction, the increased infectivity may produce equivalency or even a net gain in the cases of hyposmia or anosmia, because a much larger number of people will become infected with the omicron variant [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The omicron variant has been reported to cause less anosmia than the preceding SARS-CoV-2 virus variants [1][2][3][4]. Since the prevalence of olfactory dysfunction varies greatly between studies, the global prevalence of anosmia caused by omicron has not yet been estimated.…”
Section: Introductionmentioning
confidence: 99%